Enantioselective Radical Alkynylation of C(sp3)‐H Bonds Using Sulfoximine as a Traceless Chiral Auxiliary. Issue 1 (1st October 2014) - Nagatomo, Masanori; Yoshioka, Shun; Inoue, Masayuki
Abstract Enantioselective alkynylation of C(sp3)H bonds adjacent to a nitrogen atom has been achieved using only chiral p‐tolyl tert‐butyldimethylsilylethynyl sulfoximine and benzophenone under photo‐irradiation conditions. A two‐carbon alkyne unit was chemo‐ and enantioselectively transferred at the nitrogen‐substituted methylene to produce the optically active propargylic amines of various structures. Remarkably, the NH‐unprotected sulfoximine group efficiently transmits its stereochemical information to the product and functions as a traceless chiral auxiliary.